Hajdu-Cheney Syndrome: First Case Report from Bangladesh (Bangladesh Journal of Child Health, 2012)
Hajdu-Cheney syndrome is an extremely rare genetic disorder of the connective tissue characterized by severe and excessive bone resorption leading to osteoporosis and a wide range of other potential symtromes. The clinical presentation and typical radiological features help in confirming the diagnosis. Hajdu-Cheney syndrome had not been reported previously in our country. Because of the rarity of the problem, we are interested to report a case of Hajdu-Cheney syndrome who was admitted in Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13086 Bangladesh J Child Health 2012; Vol 36 (2): 98-100